Old Testament exegesis : a handbook for students and pastors - Stuart, Douglas K. (Louisville, KE : Westminster/John Knox, 2002)
Includes bibliographical references.
First ed. published 1980 ; 2nd ed. published 1984, which see also.
Keywords: Bible. -- criticism, interpretation, etc